2018
DOI: 10.1016/j.stemcr.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Characterization of Calcium Handling in Human Induced Pluripotent Stem Cell-Derived Atrial Cardiomyocytes

Abstract: SummaryHuman induced pluripotent stem cell (hiPSC)-derived atrial cardiomyocytes (CMs) hold great promise for elucidating underlying cellular mechanisms that cause atrial fibrillation (AF). In order to use atrial-like hiPSC-CMs for arrhythmia modeling, it is essential to better understand the molecular and electrophysiological phenotype of these cells. We performed comprehensive molecular, transcriptomic, and electrophysiologic analyses of retinoic acid (RA)-guided hiPSC atrial-like CMs and demonstrate that RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 32 publications
9
55
1
Order By: Relevance
“…Overall, the APs of our atrial-like hiPSC-CMs were substantially shorter and had a lower AP plateau than those of our ventricular-like hiPSC-CMs, in qualitative agreement with previous studies on atrial- and ventricular-like hiPSC-CMs ( Marczenke et al, 2017 ; Verkerk et al, 2017 ; Argenziano et al, 2018 ; Cyganek et al, 2018 ; Lemme et al, 2018 ; Veerman et al, 2019 ). There are some quantitative differences in AP parameters with previous studies, but these are likely due to differences in cell lines, differences in differentiation protocols, absence or presence of I K 1 injection, and a different definition of AP plateau amplitude.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the APs of our atrial-like hiPSC-CMs were substantially shorter and had a lower AP plateau than those of our ventricular-like hiPSC-CMs, in qualitative agreement with previous studies on atrial- and ventricular-like hiPSC-CMs ( Marczenke et al, 2017 ; Verkerk et al, 2017 ; Argenziano et al, 2018 ; Cyganek et al, 2018 ; Lemme et al, 2018 ; Veerman et al, 2019 ). There are some quantitative differences in AP parameters with previous studies, but these are likely due to differences in cell lines, differences in differentiation protocols, absence or presence of I K 1 injection, and a different definition of AP plateau amplitude.…”
Section: Discussionsupporting
confidence: 92%
“…Potentially, this could have an effect on the plateau phase of the AP. It has also been reported that atrial-like hiPSC-CMs have lower expression of CACNA1C, as well as reduced peak I Ca,L amplitude and current density [49]. However, the precise functional roles of the antisense and intronic transcripts we identified remain unclear.…”
Section: Discussionmentioning
confidence: 81%
“…Coupling between CF and cardiomyocytes can either promote or suppress cardiac alternans, depending on two competing effects on repolarization and Ca 2+ cycling [ 69 ]. Further, cardiomyocytes with a relatively immature set of calcium-handling proteins, as is likely found in hiPSC-CMs [ 70 ], may be more prone to alternans due to an inability to effectively regulate calcium current ( I Ca ), which is a major driver of alternans [ 71 ]. In our data set, the pacing frequency at which alternans onset occurs increases with dose-dependent hCF inclusion ( Figure 5(c) ), likely due to the higher maximum capture rates of higher percentage hCF tissues.…”
Section: Discussionmentioning
confidence: 99%